True confessions of a heartless girl - Brooks, Martha, 1944- (New York : Farrar Straus Giroux, 2003)
A confused seventeen-year-old girl, a single mother and her young son, two elderly women, and a sad and lonely man, with their own individual tragedies to bear, come together in a small Manitoba town and find a way to a better future.
"First published in Canada by Groundwood Books"--T.p. verso.
"Melanie Kroupa Books.".
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: City and town life -- Fiction; Interpersonal relations -- Juvenile fiction; City and town life -- Fiction; Interpersonal relations -- Fiction; City and town life -- Fiction; Interpersonal relations -- Fiction; Canada -- Juvenile fiction; Manitoba -- Juvenile fiction; Canada -- Fiction; Manitoba -- Fiction; Canada -- Fiction; Manitoba -- Fiction